Partisipasi Peserta Didik Dalam Pemilihan Ketua OSIS - Putri, Afrilia Dinianti (Jurnal Mahasiswa Karakter Bangsa, 2023)
An application of civic education and Pancasila courses that cover democracy and participation is students voting for the OSIS chairperson. The OSIS chairperson is chosen every year at one of the private junior high schools in South Tangerang. Only about 73% of students cast ballots in the OSIS chairperson election held at the At-Taqwa Islamic Middle School in South Tangerang in 2022, according to the data that was available at the time. In order to learn more about how students engaged in the OSIS chairman election held at At-Taqwa Islamic Middle School in 2023, research on student involvement in the election of the OSIS chairman was conducted. Since students were encouraged to exercise their right to vote by Pancasila and civics education teachers, there was a 15% increase in student participation in the election of the OSIS chairman at At-Taqwa Islamic Middle School as a result of this study's qualitative methodology. If this finding is confirmed, it would indicate that student participation in the election of OSIS chairmen at At-Taqwa Islamic Middle School is increasing. In this way, it is hoped that in the future teachers will always encourage students to participate and exercise their voting rights.